Integrasi Etika, Moral, dan Akhlak Dalam Kehidupan Bermasyarakat - Selviani, Andini; Adelia Calosa, Flora; Safitri Maharani, Nabila; Ardhian Rafi’i, Reyes; Setia Ani, Sari; Ghozali, Imam (UNIVERSITAS SERAMBI MEKKAH, 2025)
Integration of Ethics, Morals and Morality in community life is an important key in creating a harmonious and civilized social order. Therefore, this study aims to explore the understanding of how ethical, moral and moral values can be applied in everyday life, and emphasizes the importance of character-based education that strengthens moral, ethical and moral values in Islam. This research method was carried out with a qualitative approach, this study obtained data from Google Form with 20 informants. The results of the study showed that the application of these values plays a significant role in forming a tolerant and responsible personality. In addition, character-based education that integrates Islamic religious values has proven effective in instilling awareness of the importance of behaving in accordance with social norms and religious teachings.